2015
DOI: 10.5194/nhess-15-35-2015
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and 3-D distinct element analysis of the failure mechanism of a slope under external surcharge

Abstract: Abstract. Landslide is a major disaster resulting in considerable loss of human lives and property damages in hilly terrain in Hong Kong, China and many other countries. The factor of safety and the critical slip surface for slope stabilization are the main considerations for slope stability analysis in the past, while the detailed post-failure conditions of the slopes have not been considered in sufficient detail. There is however increasing interest in the consequences after the initiation of failure that in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The present solutions have given good results when compared with some previous studies and a laboratory test shown in Fig. 6, also demonstrated by Li and Cheng (2015). The laboratory test has also revealed some interesting progressive failure phenomenon and deformation characteristic for this slope failure problem.…”
Section: Y M Cheng Et Al: Three-dimensional Slope Stability Problemsupporting
confidence: 79%
See 1 more Smart Citation
“…The present solutions have given good results when compared with some previous studies and a laboratory test shown in Fig. 6, also demonstrated by Li and Cheng (2015). The laboratory test has also revealed some interesting progressive failure phenomenon and deformation characteristic for this slope failure problem.…”
Section: Y M Cheng Et Al: Three-dimensional Slope Stability Problemsupporting
confidence: 79%
“…More critical slope failure problems are being faced the Chinese Government, and there are various types of slope research underway in Hong Kong, China and many other areas. The present work is part of the continuous research programme by the authors (Cheng et al, 2013b;Li and Cheng, 2015), which include the use of innovative slope stabilization methods, debris flow flume and large-scale tests, advanced theory and design practice useful for both researchers and engineers, for both natural and reinforced slopes. Slopes in front of bridge abutment are very common in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…The global stability and sliding stability of soil nail walls against ultimate limit states are also evaluated using reliability analysis based on Monte Carlo simulation technique [31]. Reinforced slope stability analysis is also done by using statistical methods, adaptive neuro fuzzy inference system (ANFIS) and distinct element analysis method (DEM) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Two different loading patterns on the shallow foundation have been carried out in the numerical simulation: a prescribed velocity or a force on a horizontal footing, representing strain controlled test and stress controlled test respectively. Since there are no major difference in the results between the two loading patterns (similar to the results for the loaded slope by Li and Cheng [31] ), the loading pattern of the strain control/velocity control will be presented in the following sections. The uniform loading was simulated by applying a vertical velocity of 0.01mm/s on the footing.…”
Section: Basic Bearing Capacity Theory Figure 1 Prandtl's Mechanismmentioning
confidence: 99%
“…The ultimate bearing capacity for shallow foundations with simple geometry has been solved by many investigators. The methods of analysis can be classified into the following four categories: (1) the limit equilibrium method [50,36,37] ; (2) the method of characteristics [44,47,21,1,6,11] ; (3) the upper/lower-bound plastic limit analysis [45,46,75,16,38,39,40,48,22,26,27,28,51,30,31,29] ; and (4) numerical methods based on either the finite-element technique (FEM) or finite-difference method [20,33,17] . For the first three groups of methods, only the ultimate condition is considered, and a simple perfectly plastic soil model is commonly assumed.…”
Section: Testmentioning
confidence: 99%